The Influence of Training and Career Development on Employee Performance Mediated by Organizational Culture at PT. Astra International Tbk. BMW Makassar - Dinda Intan Maharani; Muh. Idrus Taba; Andi Reni (International Journal of Social Science, Education, Communication and Economics (SINOMICS JOURNAL), 2023)
PT. Astra International Tbk BMW Makassar is the subject of the study, aimed at conducting an in-depth investigation into the impact of training and career expansion factors on employee performance, mediated by the business culture factor. A total of 120 employees participated as respondents, and data were collected through questionnaire surveys, non-participant observation, and interviews. Path analysis will be utilized to justify the impact of exogenous factors on endogenous factors. The study's findings revealed significant direct effects in the path of substruktur 1, indicating that career expansion (X2) has a significant impact on workforce performance. Additionally, the exogenous factor of career expansion has a substantial and direct impact on the business entity's culture in path substruktur 2. In path substruktur 3, it was observed that training has a significant and substantial impact on career expansion. Subsequently, the Sobel test was employed to explore the non-contingent impact of training on employee performance, mediated by the organizational culture, which showed a significant and direct relationship. Similarly, the non-contingent impact of career expansion on employee performance, mediated by the organizational culture, demonstrated a significant and direct association.